Determinasi Teknologi Harga Dinamis dalam Komunikasi: Studi Kasus pada Aplikasi Online Travel di Indonesia - Maria Risa Puspitasari; Velisia Serenada; Irwansyah Irwansyah (Jurnal Komunikasi dan Ilmu Sosial, 2026)
This study examines on AI‑based dynamic pricing practices in an Indonesian online travel mobile application as a socio‑technical phenomenon that combines technological, economic, and price‑communication logics. The research adopts a qualitative case study approach, using in‑depth interviews with three key informants from the data/AI, product pricing, and revenue management divisions, complemented by document analysis. The findings show that automation becomes a primary necessity due to scalability demands, making manual management of millions of inventories impossible and driving a transition from rule‑based systems to machine‑learning models. Algorithms manage prices and subsidies based on demand, competitor pricing, and users’ willingness to pay, while human agency is maintained through guardrails, thresholds, feedback loops, and manual interventions. Dynamic pricing is communicated through scarcity messages, transparent presentation of costs to consumers, automated notifications when prices change, and incentives designed to mitigate perceptions of unfairness. The study concludes that this practice operates within a soft determinism framework and recommends strengthening algorithm governance, communicative transparency, and dynamic‑pricing literacy programs for consumers.